Oral rehydration therapy: efficacy of sodium citrate equals to sodium bicarbonate for correction of acidosis in diarrhoea. Issue 8 (August 1984) - Islam, M R; Samadi, A R; Ahmed, S M; Bardhan, P K; Ali, A
Abstract : Forty patients with moderate degrees of dehydration and acidosis because of acute watery diarrhoea were successfully treated randomly with either WHO recommended oral rehydration solution containing 2.5 g sodium bicarbonate or an oral solution containing 2.94 g sodium citrate in place of sodium bicarbonate per litre of oral rehydration rehydration solution. Efficacies were compared by measuring oral fluid intake, stool and vomitus output, change in body weight, hydration status, and rate of correction of acidosis during a period of 48 hours. Seventy five per cent (21 cases) in the citrate group and 83% (19 cases) in the bicarbonate group were successfully rehydrated (p greater than 0.05). There were no significant differences in intake, output, gain in body weight, fall in haematocrit and plasma specific gravity, and correction of acidosis between the two groups of patients within 48 hours after initiation of therapy. The solution with sodium citrate base was as effective as WHO-oral rehydration solution for management of diarrhoea. This study shows the efficacy, safety, and acceptability of citrate containing oral rehydration solution for rehydration and correction of acidosis in diarrhoea.